2019
DOI: 10.1183/23120541.00209-2018
|View full text |Cite
|
Sign up to set email alerts
|

The characterisation of interstitial lung disease multidisciplinary team meetings: a global study

Abstract: Multidisciplinary team (MDT) diagnosis of interstitial lung disease (ILD) has been proposed as a gold standard, but there are no formal recommendations for MDT process or composition and limited knowledge regarding prevalence in routine practice.We performed a systematic evaluation of ILD diagnostic practice across a range of healthcare settings around the world. Electronic questionnaires were distributed across all global regions via society and collaborators networks.Responses from 457 unique centres across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 14 publications
1
60
0
2
Order By: Relevance
“…Although adopted worldwide, there are no formal recommendations for an MDA process or its composition. Thus, a “minimum MDA standard” is still hard to define (6), and the low agreement among MDAs for ILDs other than idiopathic pulmonary fibrosis remains a concern (7). As concerns our study, a 1-year follow-up diagnostic review of all 21 patients in the article (often seen as an acceptable gold standard) demonstrated perfect agreement with diagnoses as published; no later changes in diagnosis/management were observed.…”
mentioning
confidence: 99%
“…Although adopted worldwide, there are no formal recommendations for an MDA process or its composition. Thus, a “minimum MDA standard” is still hard to define (6), and the low agreement among MDAs for ILDs other than idiopathic pulmonary fibrosis remains a concern (7). As concerns our study, a 1-year follow-up diagnostic review of all 21 patients in the article (often seen as an acceptable gold standard) demonstrated perfect agreement with diagnoses as published; no later changes in diagnosis/management were observed.…”
mentioning
confidence: 99%
“…The official ATS/ERS/JRS/ALAT clinical practice guidelines recommend a dynamic process of MDT in the management of ILD since individual decisions on complex cases may increase the risk of delayed diagnosis, inappropriate treatment or unnecessary additional diagnostic testing [4]. Although one ILD case out of five can be related to SARD, a recent systematic evaluation of diagnostic ILD practice around the world showed that only 37.1% of MDT cases include a rheumatologist [5]. The clinical impact of this practice is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary team (MDT) evaluation has been proposed as the gold standard [4] in the management of ILD. Nonetheless, there are no formal recommendations for its composition and working process [5]. Even if current guidelines consider it mandatory to exclude a systemic autoimmune rheumatic disease (SARD) in any newly diagnosed ILD, a rheumatologist is not routinely involved in MDT.…”
Section: Introductionmentioning
confidence: 99%
“…ILD diagnosis is established by a multidisciplinary team of respirologists, chest radiologists, and lung pathologists based on a combination of clinical information derived from pulmonary function tests, chest imaging, and lung tissue histology (Richeldi et al, 2019). CPET data are not a requirement for a multidisciplinary diagnosis of ILD but may be used to inform patient management.…”
Section: Current Use Of Cpetmentioning
confidence: 99%